2007
DOI: 10.1007/s00211-007-0113-y
|View full text |Cite
|
Sign up to set email alerts
|

Preserving exponential mean-square stability in the simulation of hybrid stochastic differential equations

Abstract: Positive results are derived concerning the long time dynamics of fixed step size numerical simulations of stochastic differential equation systems with Markovian switching. Euler-Maruyama and implicit theta-method discretisations are shown to capture exponential mean-square stability for all sufficiently small time-steps under appropriate conditions. Moreover, the decay rate, as measured by the second moment Lyapunov exponent, can be reproduced arbitrarily accurately. New finite-time convergence results are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Theorem 5.5 shows that the EM approximation (4.2) can reproduce the mean-square exponential stability of the exact solution without the global Lipschitz condition. This improves the existing results about the numerical stability of nonlinear hybrid systems in the sense of moments (see [7,10,18]). …”
Section: Em Methodssupporting
confidence: 80%
“…Theorem 5.5 shows that the EM approximation (4.2) can reproduce the mean-square exponential stability of the exact solution without the global Lipschitz condition. This improves the existing results about the numerical stability of nonlinear hybrid systems in the sense of moments (see [7,10,18]). …”
Section: Em Methodssupporting
confidence: 80%
“…The converse question is: if the numerical method is exponentially stable in moment or almost surely for small , can we infer that the underlying hybrid SDE is exponentially stable in moment or almost surely? It is only recently that Higham et al [8] have positively answered this question for mean-square exponential stability. It is not very difficult to develop their techniques to cope with the pth moment exponential stability for p 1 while it would be a challenge for p ∈ (0, 1) although it is highly possible given the techniques developed in [19].…”
Section: Further Commentsmentioning
confidence: 98%
“…Recently, Zhu and Chu [51] presented the numerical methods for a mean-square exponential dichotomy (MS-ED) of a linear SDE and showed that the MS-ED is equivalent to the numerical results for sufficient small step sizes under natural conditions. We also refer to [18,23,24,52] for more related results and techniques about this topic.…”
Section: Introductionmentioning
confidence: 99%